Developing an approach to the performance-oriented testing of science teachers' action-related competencies. Issue 14 (22nd September 2019) - Bartels, Hauke; Geelan, David; Kulgemeyer, Christoph
ABSTRACT: Measuring teachers' skills to carry out the complex tasks required in teaching is an important means of evaluating the effectiveness of teacher education but remains a challenging activity to conduct in practice. It is necessary to optimise approaches for usability and effectiveness along a continuum from low-effort and low-authenticity measures such as paper-and-pencil tests to high-effort, high-authenticity measures such as extended classroom observations. The first part of the paper reviews a range of efforts toward measuring the competencies of teachers and other professionals in carrying out the tasks that make up their work. These include performance tests such as computer-based simulations or simulations using actors, as well as the use of tasks requiring participation in or responses to video vignettes. Video vignette approaches typically have been less interactive than performance tests and interactivity is seen as a desirable feature. A novel framework for developing performance-oriented testing is then outlined. The second part of the paper exemplifies this framework in relation to providing explanations in physics classrooms. The development of a novel test instrument following the framework is described, and findings on construct validity are presented to support the applicability of the presented approach.